2013
DOI: 10.5897/ajps12.167
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure in summer of Tehsil Takht-e-Nasrati plains, district Karak, Pakistan

Abstract: Community structure is a key marker of long-term vegetation change in ecosystem. In the present investigation, 11 plant communities were recorded in plains area. The cluster analysis gives rise to 5 groups on the basis of important value and 4 groups on basis of soil. The vegetation changed with change of distance. As a whole in plains, the CZS community was developed. There were 6 tree, 7 shrub and 19 herb species. The Importance value contributed by three dominants species was 79.5. The contribution by tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…act as reducing agents for Ag + to generate NPs [12]. Recently reported plant extracts that were used for biosynthesis of AgNPs included Urtica diocia [13], Tropaeolum majus [14], Skimmia laureola [15], Azadirachta indica [16], and Araucaria angastifolia [17].…”
Section: Introductionmentioning
confidence: 99%
“…act as reducing agents for Ag + to generate NPs [12]. Recently reported plant extracts that were used for biosynthesis of AgNPs included Urtica diocia [13], Tropaeolum majus [14], Skimmia laureola [15], Azadirachta indica [16], and Araucaria angastifolia [17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors [7] research out the phytosociology of roadside communities and as a result 85 species were observed. The authors [8] reported 11 plants community during summer in Tehsil Takht-E-Nasrati Hills, District Karak, Pakistan. The author [9] studied the Maturity dynamism of plant life and pointed out that the species frequency was changed with the change of season and altitude.…”
Section: Introductionmentioning
confidence: 99%
“…It improves the soil infiltrations, structure and prevents erosion. The authors [8,27,28], described that the resources of soil is limited and its physical and chemical properties are restricted mostly by humus and clay. Several research works dealing with different features of plant life from diverse parts of the state have been taken out form time to time [16,19,21,22,29].…”
mentioning
confidence: 99%
See 1 more Smart Citation